Trophic state of the wetland “Gota e´Leche, Yotoco, Valle del Cauca state, Colombia. Based on biological, physichal and chemical parameters - Juan Díaz P; Guido Ortiz F; Rubiel Caicedo N; Leonidas Zambrano P,; Hilldier Zamora; Gerardo Naundorf, (Revista Colombiana de Ciencia Animal Recia, 2017)
One of the most representative wetlands Cauca Valley State is the one called “Gota e’ Leche”, located in the town of Yotoco. This ecosystem is important because it is the habitat of many species of animals and native plants. The region where is located is a tropical dry forest (Bs-T) (HOLDRIDGE, 1978). The wetland has had numerous trophic changes because the anthropogenic activities carry on the area (sugar mills, farmers, etc.), This study determined the trophic state of the wetland using biological parameters such as primary productivity, chlorophyll, riparian flora and aquatic macro invertebrates, as well as physical and chemical such as water temperature, salinity, dissolved gases and others. According to our data, we determined that the wetland has a eutrophic state prone to hyper eutrophication. The system is continuously subjected to disturbance by human activities that change the characteristics of the ecosystem. As an indicator of this change, it is noticeable that in some sectors the marshy vegetation shows succession process belonging to a transition between aquatic and terrestrial ecosystems. For this reason, it is important the get more and meaningful knowledge of their successional stage in order to implement actions that will enable their restoration and conservation.